2013
DOI: 10.1080/15434303.2011.642040
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Transparent Construct of Reading-to-Write Tasks: The Interface Between Discourse Features and Proficiency

Abstract: As a growing number of testing programs use integrated writing tasks, more validation research is needed to inform stakeholders about score use and interpretation. The current study investigates the relationship between writing proficiency and discourse features in an integrated reading-writing task. At a Middle Eastern university, 136 undergraduate students completed a reading-based writing task. The essays were holistically scored by two raters and then classified into three proficiency levels. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 34 publications
5
48
1
7
Order By: Relevance
“…Thus, the findings confirm those of previous studies, which found that prompt characteristics can affect the quality of EAP students' written texts (Cho et al, 2013;Cumming et al, 2005;Gebril & Plakans, 2013). However, there was no correlation between the essay ratings and the lexical breadth, word accessibility, or AWL usage in the students' texts, which does not support the findings of previous research (Crossley, Salsbury, et al, 2011).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Thus, the findings confirm those of previous studies, which found that prompt characteristics can affect the quality of EAP students' written texts (Cho et al, 2013;Cumming et al, 2005;Gebril & Plakans, 2013). However, there was no correlation between the essay ratings and the lexical breadth, word accessibility, or AWL usage in the students' texts, which does not support the findings of previous research (Crossley, Salsbury, et al, 2011).…”
Section: Discussioncontrasting
confidence: 52%
“…However, these studies did not analyze integrated-writing tasks, but instead used independent writing tasks such as free writing and narratives. Although integrated-writing assessment studies have demonstrated that lexical features differentiate essays at rating levels (Cumming et al, 2005), other research studies have reported no difference in lexical diversity features based on essay rating (Gebril & Plakans, 2013). Furthermore, studies of prompt characteristics have shown that prompt variation in terms of the difficulty of source texts impacts the text ratings (Cho et al, 2013).…”
Section: La Présente éTude a Comparé Des Rédactions éCrites Par Desmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, with integrated tasks becoming more popular (e.g. Gebril & Plakans, 2013;Plakans, 2009), it is also important for test providers to show that different tasks in a speaking test in fact elicit different discourse types from test takers. If no differences were found, test developers would lack evidence for including extra tasks.…”
Section: Task Effectsmentioning
confidence: 99%
“…More recently, with integrated tasks becoming more popular (e.g. Gebril & Plakans, 2013;Plakans, 2009), it is also important for test providers to show that different…”
Section: Task Effectsmentioning
confidence: 99%